2004
DOI: 10.1161/01.res.0000126922.18222.f0
|View full text |Cite
|
Sign up to set email alerts
|

Arteriogenesis Proceeds via ICAM-1/Mac-1- Mediated Mechanisms

Abstract: Monocyte adhesion to shear stress-activated endothelium stands as an important initial step during arteriogenesis (collateral artery growth). Using multiple approaches, we tested the hypothesis that monocyte adhesion via intercellular adhesion molecule-1 (ICAM-1) and selectin interactions is essential for adaptive arteriogenesis. Forty-eight New Zealand White rabbits received either solvent, monocyte chemoattractant protein-1 (MCP-1) alone, MCP-1 plus ICAM-mab, or MCP-1 plus an IgG2a isotype control via osmoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 40 publications
5
136
0
3
Order By: Relevance
“…Here, DNMT1 inhibition increased arteriogenic capacity by ≈44% in nonreversed segments, while there was no effect on reversed flow segments ( P =0.163), indicating that this response is not limited to the C57BL/6 strain. We also sought to determine whether this increased arteriogenic capacity in nonreversed flow segments following DNMT1 inhibition corresponded to altered macrophage recruitment, a necessary component of collateral artery growth45, 46, 47, 48, 49, 50, 52 in vivo. Nonreversed flow collateral segments exhibited a trend ( P =0.057) toward increased pericollateral Mac3 + macrophages in 5AZA‐treated mice (day 17 post FAL, 3 days of 5AZA treatment), corresponding to our previous in vitro results (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Here, DNMT1 inhibition increased arteriogenic capacity by ≈44% in nonreversed segments, while there was no effect on reversed flow segments ( P =0.163), indicating that this response is not limited to the C57BL/6 strain. We also sought to determine whether this increased arteriogenic capacity in nonreversed flow segments following DNMT1 inhibition corresponded to altered macrophage recruitment, a necessary component of collateral artery growth45, 46, 47, 48, 49, 50, 52 in vivo. Nonreversed flow collateral segments exhibited a trend ( P =0.057) toward increased pericollateral Mac3 + macrophages in 5AZA‐treated mice (day 17 post FAL, 3 days of 5AZA treatment), corresponding to our previous in vitro results (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…We also examined surface adhesion molecule expression on circulating monocytes by flow cytometry and on the aortic endothelium by immunohistochemistry, because several of these molecules have been shown to be critically important in monocyte recruitment into vessel walls (22,28,35,46). The selectin group of adhesion molecules are involved in monocyte rolling and tethering to activated endothelium, while the integrins (CD18/CD11, VLA-4) are required for firm adhesion to proteoglycans and immunoglobulin molecules (ICAM-1 and VCAM-1) on the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of monocyte recruitment, changes in adhesion molecules on monocytes are involved in leukocyte tethering, rolling (E-and L-selectin), firm adhesion (CD11/CD18 integrins), and transmigration [very late antigen (VLA)-4, platelet endothelial cell adhesion molecule (PECAM)-1] by interacting with molecules on the endothelium [intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM) -1]. The expression of these various surface antigens is modulated by inflammatory cytokines (22,28,35,46).…”
mentioning
confidence: 99%
“…In recent studies, we have shown that Icam1 is differentially expressed during arteriogenesis and that blunted Icam1 expression as well as Icam1 deficiency is associated with less effective arteriogenesis and perivascular accumulation of macrophages. [4][5][6] In the current study, our qRT-PCR results demonstrated that administration of nor-NOHA abolished the differential expression of Icam1 in growing collaterals. These data are in accordance with results from Giri et al 31 showing that downregulation of arginase 2 in human umbilical vein endothelial cells abrogated leukocyte adhesion by blocking the expression of Icam1.…”
Section: Arginase Inhibition In Arteriogenesismentioning
confidence: 62%
“…3 Animal models, mainly for peripheral arteriogenesis, evidenced that increased shear stress results in activation of the arteriolar endothelium with subsequent upregulation of monocyte chemoattractant protein-1 (MCP-1) as well as ICAM1 presenting the prerequisite for monocyte recruitment, adhesion, and extravasation. [4][5][6] After extravasation, monocytes mature to macrophages, whereby M1 as well as M2 macrophages have been described to contribute to vascular remodeling. 7 Interestingly, it has been shown that exogenously administrated nitric oxide (NO) donors promote arteriogenesis.…”
mentioning
confidence: 99%